#### Answer

$2$

#### Work Step by Step

$\ln \left( 6x\right) -\ln \left( x+1\right) =\ln 4\Rightarrow \ln \dfrac {6x}{x+1}=\ln 4\Rightarrow \dfrac {6x}{x+1}=4$
$\Rightarrow 6x=4x+4\Rightarrow 2x=4\Rightarrow x=2$

Published by
Pearson

ISBN 10:
013421742X

ISBN 13:
978-0-13421-742-0

$2$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.